2022
DOI: 10.11646/zootaxa.5120.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of geckos of the genus Phyllopezus Peters, 1878 (Squamata: Gekkota: Phyllodactylidae) from northeastern Brazil

Abstract: We describe two new species of Brazilian geckos of the genus Phyllopezus based on morphological and molecular data. The first species is currently known from a relictual Cerrado enclave—“campos rupestres”, in the mountains of the Serra do Espinhaço in the state of Bahia. The second species is known from northeastern Atlantic Forest and transitional areas with Caatinga biome in the state of Alagoas. The two new species are sister taxa and together are the sister clade to the remaining species in the Phyllopezus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In general, we found high species dissimilarity between the studied areas and we showed that the four grouped areas shelter about 53% of the species known to inhabit areas of Caatinga vegetation (which covers about 845,000 km 2 ) (Gonçalves-Sousa et al, 2022) and 33% of all lizard species that occur in the semiarid region of Northeast Brazil (1,128,697 km 2 ) (Dubeux et al, 2022;Mesquita et al, 2017).…”
Section: Con Cluding Remark Smentioning
confidence: 69%
See 1 more Smart Citation
“…In general, we found high species dissimilarity between the studied areas and we showed that the four grouped areas shelter about 53% of the species known to inhabit areas of Caatinga vegetation (which covers about 845,000 km 2 ) (Gonçalves-Sousa et al, 2022) and 33% of all lizard species that occur in the semiarid region of Northeast Brazil (1,128,697 km 2 ) (Dubeux et al, 2022;Mesquita et al, 2017).…”
Section: Con Cluding Remark Smentioning
confidence: 69%
“…In general, we found high species dissimilarity between the studied areas and we showed that the four grouped areas shelter about 53% of the species known to inhabit areas of Caatinga vegetation (which covers about 845,000 km 2 ) (Gonçalves‐Sousa et al, 2022) and 33% of all lizard species that occur in the semiarid region of Northeast Brazil (1,128,697 km 2 ) (Dubeux et al, 2022; Mesquita et al, 2017). These findings underline the substantial conservation value of these four areas and the need to consider studies related to the ecological niche of ectothermic animals with low dispersion, such as lizards, in the development of management plans and strategies for land use and occupation.…”
Section: Discussionmentioning
confidence: 86%
“…‘Cryptic’ diversity is frequent in Neotropical phyllodactylid geckos (Cacciali, Lotzkat, et al, 2018; Domingos et al, 2014; Dubeux et al, 2022; Gamble et al, 2012). Indeed, morphological conservatism is so remarkable in these organisms that is has been recently shown that Homonota and Garthia share a great majority of both external and internal character states (Daza et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, cryptic species harbour a ‘hidden diversity’ that may reflect recent divergence, niche conservatism, parallelism or convergence (Fišer et al, 2018; Korshunova et al, 2019; Struck et al, 2018). Cryptic lineages are very frequent among Neotropical lizards from different families, for example Alopoglossidae (Ribeiro‐Júnior et al, 2020), Dactyloidae (Guarnizo et al, 2016), Phyllodactylidae (Cacciali, Lotzkat, et al, 2018; Domingos et al, 2014; Dubeux et al, 2022), Sphaerodactylidae (Pinto et al, 2019), Teiidae (Arias et al, 2018; Giugliano et al, 2013) and Tropiduridae (Teixeira Jr et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The species is found in rocky outcrops and trees. Were mainly observed active in the early evening when foraging in forested sites near rivers with rocky bed(Dubeux et al 2022). Diet based mainly on arthropods, no information about the preferred items on the diet of this species is known(Albuquerque et al 2013;Palmeira et al 2021).Figure 8.…”
mentioning
confidence: 99%